1995
DOI: 10.1177/039139889501800304
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Blood Salvage (IOBS) in Cardiac and Vascular Surgery

Abstract: The extensive application of IOBS has permitted a great reduction in the use of homoglous transfusion which presently represents the largest field of application of autologous systems. In cardiac and vascular surgery, IOBS is particularly useful to the goal of preventing the transmission of viral disorders and other adverse effects related to homologous transfusions. The apparatuses for IOBS may also be used to perform hemodilution and sequestration of a desired amount of platelet rich plasma. The appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Several animal studies have shown the benefit and potential of APG for the treatment of skin burns, 9 bone defects around dental implants, 10,11 and oral and maxillofacial reconstruction. 12,13 Some reports demonstrated clinical effect of PRP and APG in cosmetic surgery, 14 cardiac surgery, [15][16][17] and mostly in oral and maxillofacial surgery. 18 -20 Up to now, it has not been reported in the treatment of fractures or nonunions of the long bones.…”
mentioning
confidence: 99%
“…Several animal studies have shown the benefit and potential of APG for the treatment of skin burns, 9 bone defects around dental implants, 10,11 and oral and maxillofacial reconstruction. 12,13 Some reports demonstrated clinical effect of PRP and APG in cosmetic surgery, 14 cardiac surgery, [15][16][17] and mostly in oral and maxillofacial surgery. 18 -20 Up to now, it has not been reported in the treatment of fractures or nonunions of the long bones.…”
mentioning
confidence: 99%
“…Кровопотери при онкохирургических вмешательствах зачастую могут достигать по объему 2-3 должных ОЦК, особенно при мультиорганных поражениях или когда в онкологический процесс вовлечены магистральные сосуды [21,22]. С другой стороны, риск попадания жизнеспособных опухолевых клеток в реинфузат и, как следствие, в системный кровоток пациента является абсолютно реальным, а экспериментальные исследования на лабораторных животных подтвердили способность этих опухолевых клеток вызывать рост вторичных метастатических узлов опухоли [22][23][24][25]. Конечно, справедливости ради следует признать, что наличие опухолевых клеток в крови пациента не является феноменом, идентичным метастазированию.…”
Section: онкологияunclassified
“…At the university hospital of Regensburg IBS with blood irradiation has been used for 9 years in cancer surgery [1]. In Europe, about 30-40 other hospitals meanwhile have adopted this method as well [20][21][22][23]. The main indications are liver surgery, bone tumors and metastases, and radical prostatectomy (table 2).…”
Section: Blood Irradiation For Elimination Of Contaminating Tumor Cellsmentioning
confidence: 99%